Mediating Effect of Happiness at Work in the Relationship between Transformational Leadership and Job Performance: A Literature Review - Angela Denise Pojanes; Genaro Japos (Philippine Association of Institutions for Research, Inc., 2022)
This study aimed to examine scientific articles as the basis for a literature review on the possible Mediating Effect of Happiness at Work in the Relationship between Transformational Leadership and Job Performance in the Philippines' Business Process Outsourcing (BPO) industry. The study used a qualitative method using a literature review that applies the content of scientific articles from reputable databases such as Google Scholar and many other websites. The results of the study show that happiness at work doesn't exert a mediating relationship between transformational leadership and job performance. However, this concludes that happiness at work has exerted a significant and positive effect on job performance.